2011
DOI: 10.1016/j.ajhg.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Myosin Light Chain Kinase Cause Familial Aortic Dissections

Abstract: In Figure 2B, the label on the right should be NR1-S560dup/NR2B instead of the alternative terminology NR1 (S560_T561InsS)/NR2B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 1 publication
4
99
0
4
Order By: Relevance
“…Because aortic dissection related to variants in MYLK often presents without a history of aortic enlargement, the ACMG StAteMent intervention of echocardiogram may be falsely reassuring and may not prevent sudden cardiac death. 8 In addition, there is insufficient evidence on the appropriate age to begin medications and the efficacy of this intervention to reduce dynamic stress on the aorta. 9 The SFWG considered that additional data on MYLK are likely to be gathered in the coming years from aneurysm genetic testing panels, and this evidence could be reevaluated periodically for possible re-addition of MYLK to the SF list.…”
Section: Resultsmentioning
confidence: 99%
“…Because aortic dissection related to variants in MYLK often presents without a history of aortic enlargement, the ACMG StAteMent intervention of echocardiogram may be falsely reassuring and may not prevent sudden cardiac death. 8 In addition, there is insufficient evidence on the appropriate age to begin medications and the efficacy of this intervention to reduce dynamic stress on the aorta. 9 The SFWG considered that additional data on MYLK are likely to be gathered in the coming years from aneurysm genetic testing panels, and this evidence could be reevaluated periodically for possible re-addition of MYLK to the SF list.…”
Section: Resultsmentioning
confidence: 99%
“…7 Of these nine variants, six are germline variants, and four of these six are reported in association with TAAD (Table 1). 7 Of note, the p.Arg1480Ter and the p.Ser1759Pro variants are listed from the article published by Wang et al 5 Here we report the case of a 25-year old man who died unexpectedly due to an ascending aortic dissection and rupture. Genetic counseling and testing were performed following his death.…”
Section: Introductionmentioning
confidence: 98%
“…In 2010, Wang et al reported two variants in the MYLK gene as likely pathogenic given the predicted damaging effects and the segregation within the families. 5 Although transcribed in all tissues, MYLK is mostly expressed in smooth muscle. 6 MYLK encodes for the myosin light chain kinase (MLCK) enzyme, which plays a crucial role in smooth muscle cell contraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MYLK was discovered by a candidate gene sequencing approach. 10 Mutations in SMAD3 were first identified by traditional linkage analysis followed by candidate gene sequencing in patients with syndromic TAAD. 7 Later on SMAD3 mutations were also discovered by whole-exome sequencing in familial non-syndromic TAAD.…”
Section: Introductionmentioning
confidence: 99%